PENETAPAN KADAR VITAMIN C CABAI PAPRIKA (Capsicum annum L. Var Grossum) HIJAU, KUNING DAN MERAH YANG BERASAL DARI CIKAJANG GARUT DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Dani Sujana (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Chili is a vegetable as well as a kitchen spice that is almost always present in everyday food. One of the types of chili that has many benefits and nutritional content that is useful for the body is paprika (Capsicum annuum L. var Grossum). Chili peppers are rich in vitamin C even higher content than oranges. Vitamin C content in paprika was determined by UV-Visible spectrophotometric method. Analysis with UV-Vis spectrophotometer was carried out for various reasons, including simpler, more specific, more accurate and more precise operating principles which were developed and validated mainly for simultaneous and more specific evaluation to determine vitamin C levels. green, yellow and red. The results showed that the highest vitamin C levels were in red chili peppers, the value of vitamin C levels in green peppers was 11.67 mg/100 g, yellow peppers were 19.15 mg/100 g, and red peppers were 29,96 mg/100 g.